Խորհրդային կոմունիստների համագումարը - Գ. Մ. Այվազյան (Հայկական ԽՍՀ գիտությունների ակադեմիա)
XXVIII съезд КПСС проходил в переломный период. Съездом определены основные линии партийной политики во всех главных сферах жизни советского общества. Важным документом съезда стало программное заявление XXVIII съезда КПСС «К гуманному, демократическому социализму». В нем определены задачи по обновлению партии и общества. The XXVIIIth congress of CPSU took place in a turning period. The main lines of party politics in all principal spheres of the soviet society life were determined by the congress. The important document of the congress was the programme declaration of the XXVIIIth congress CPSU "To the humane, democratic socialism". The problems on renovation of party and the society are determined in it.
Keywords: Political Science; J Political Science; JPP Political Parties